Reaction-Induced Phase Separation: A Strategy to Synthesize Azobenzene-Modified All-Optical PDLC Devices - Orofino, Antonela Beatriz (2018)
This work presents the synthesis of all-optical polymer dispersed liquid crystals (PDLC) devices, in which the reversible trans–cis photoisomerization of azobenzene groups is used to induce the transition in the liquid crystal (LC) phase, activating the film from an opaque to a translucent state. The appropriate morphology is obtained through a reaction-induced phase separation strategy using an epoxy–amine matrix modified with azobenzene precursors and the addition of a thermoplastic polymer (polystyrene, PS), which promotes the phase separation and the preferential location of the LC in separated domains. Formulations with liquid crystal content of 50 wt%, 5 wt% of modifier (PS), and 10 wt% of azo-precursor present a reversible on–off optical response when irradiating the sample with the activation beam at λ = 488 nm. It is demonstrated that the liquid crystal responds according to the expected cooperative movement of orientation with the azobenzene groups. Based on the study of the PDLC devices obtained, its potential technological application can be confirmed.